Integrating Forensic Toxicology, Clinical Laboratory Diagnostics, and Psychiatry for Comprehensive Management of Substance Abuse and Addiction in Saudi Arabia - Alhomaidhy, Majed Ali D.; Almarshedi, Majed Abdullah A.; Almasari, Salman Abdullah Sulaiman; Alnasser, Hamad Khaled Hamad; Alshahrani, Abdullah Mubarak Mohammed; Alzahrani, Raed Jamaan A.; Al-Dosari, Fahd Abdulaziz Salem; Al-Mahmoud, Mahmoud Saad Ali; Althubaiti, Badr Abdullah Saeed; Mohammed, Khawlah Yahya Z.; et al. (Journal of Posthumanism, 2024)
Substance use disorders (SUDs) are a growing public health concern in Saudi Arabia, with increasing prevalence, shifting substance abuse trends, and severe psychiatric and clinical manifestations. Despite stringent legislations, gaps remain in early identification, easier treatment access, and smooth care. Multicenter, prospective, mixed-methods studies were conducted across six tertiary centers, three forensic units, and five rehabilitation centers. Participants were 600 adults with SUDs. Toxicological screening, clinical biomarker investigations, and structured psychiatric ratings with DSM-5- and ICD-11-driven guidelines were applied during data collection. SPSS, SmartPLS, and NVivo analyzed the data statistically and in terms of thematic content. Amphetamines (30%), cannabis (26%), and methamphetamine (17%) were the most commonly identified substances, with 19% self-reporting polysubstance use. Laboratory findings revealed severe hepatic (36%) and renal (17%) impairment with metabolic disturbances. Co-morbid psychiatric conditions were highly prevalent, with depression (33%), anxiety (24%), and PTSD (9%). Multi-organ dysfunction with high relapse potential was revealed by combined risk modeling in 31% of participants. The findings reveal the imperative for interdisciplinary, patient-centered therapy integrating toxicological tracking, clinical diagnosis, and psychiatric intervention to optimize therapeutic outcomes, reduce rates of relapse, and inform country-level strategies for the management of addictions in Saudi Arabia.